Prototipe Robot SUMO Otonom dalam Mengenali Object Musuh berbasis Sensor Ultrasonic: Autonomous SUMO Robot Prototype in Recognizing Enemy Objects based on Ultrasonic Sensor - Amal, Iskariman Halmahera (Indonesian Journal of Electrical Engineering and Renewable Energy (IJEERE), 2021)
The current competition is not only done by humans, but has entered into interference from technology, one of which is robotics technology. One of the competitions is the sumo robot competition, the purpose of making this sumo robot is to be able to move independently or autonomously and be able to detect enemies and push enemies out of the arena, so that the functionalities of the robot are similar to sumo wrestlers and after that can be included in the competition. This sumo robot uses an arduino nano microcontroller as the brain of the robot, five ultrasonic sensors and two proximity sensors, in technical terms the assembly begins with the design, assembly, programming and finally testing. Robot testing is done by testing the characteristics of the movement based on sensor input. The result is the robot will react if there is an object with a radius of 75 cm from the robot and the robot also reacts when the floor surface is light colored.